360 The increasing incidence of carcinosarcoma of the ovary and fallopian tube in the united states: who is most at risk?. (13th November 2020) - Ratnaparkhi, R; Liao, C; Maxwell, L; Darcy, KM; Tian, C; Chan, J
Abstract : Introduction: The purpose of this study was to leverage a large population database to analyze trends in the incidence of carcinosarcoma of the ovary, fallopian tube, and peritoneum. Methods: Data were obtained from the United States Cancer Statistics (USCS) database from 2001 to 2016. Age-adjusted incidence per 100, 000 women and annual percent change (APC) in incidence were calculated using SEER*Stat and Joinpoint Software. Results: 9, 675, 658, and 745 women had carcinosarcoma of the ovary, fallopian tube, and peritoneum with an age-adjusted incidence of 0.33, 0.04, and 0.03 in 2016 respectively. Over a sixteen-year period, the incidence of ovarian carcinosarcoma increased 0.53% per year (95% CI 0.13, 0.94; P = 0.014), and the incidence of tubal carcinosarcoma increased 4.85% per year (95% CI 2.32, 7.43; P = 0.001). The incidence of local disease decreased 3.53% per year (95% CI -5.78, -1.23; p = 0.006) in contrast to significant increases in both regional and distant disease. The incidence of carcinosarcoma increased only in the Middle Atlantic and East North Central regions [APC 1.36%, (95% CI 0.36, 2.38), p = 0.011; APC 1.71%, (95% CI 0.60, 2.38), p = 0.005]. Non-Hispanic Blacks had the highest incidence (0.35) of carcinosarcoma and highest increase in incidence per year (1.59%). Conclusions: Although rare, the incidence of carcinosarcoma of the ovary and fallopian tube is significantly increasing in the United States, particularly for Non-Hispanic Blacks.